Uji Kepekaan Sel Biofilm Isolat Klinik Pseudomonas aeruginosa Penyebab OMSK di RSUP dr. Sardjito Terhadap Gentamicin - , ADI BAGUS ANDRIANTO; , dr. Agus Surono, Sp.THT.KL, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : P.aeruginosa is one of many bacteria that can cause Supppurative Chronic Otitis Media. It can form a biofilm which is difficult to treat because it can defend itself against various antibiotic. Objective : The objective of this research was to do a susceptibility test to a biofilm formed by P.aeruginosa on Chronic Suppurative Otitis Media patients against gentamicin in vitro. Method and Material : Design of this research is observational analitic, which is cross sectional. Biofilm susceptibility test against gentamicin done by microbroth dilution method using 96- well microplate. Concentration of gentamicin was 128, 64, 32, 16, 8, 4, 2, 1, 0.5, and 0.25 g/ml. After putting antibiotic, MTT assay is performed. Results of MTT assay is analysed with MBRC50. Results : There is no concentration founded to have absorbance below MBRC50 cut-off point. Gentamicin concentration that come close to MBRC50 cut-off is at 128 g/ml, which can reduce biofilm cell quantity of P.aeruginosa to the point of 48.5%. Conclusion : Pseudomonas aeruginosa biofilm on CSOM patients who came to THT clinic RSUP dr.Sardjito, given the gentamicin in vitro founded to have highest MBRC of 48.5% at concentration of 128 g/ml.